ANALISA PENGUKURAN KINERJA DENGAN METODE PERFORMANCE PRISM DAN OMAX DI PT. TORGANDA PKS RANTAU KASAI - Rini Halila Nasution; Uun Novalia Harahap; Yetti Meuthia Hasibuan; Deny Satria; Anggi Muhaimin (Universitas Harapan Medan, 2021)
The current performance measurement conducted by PT. Torganda PKS Rantau Kasai is a traditional performance measurement method that only focuses on the financial aspect as s benchmark for measuring performance. However, performance measurement ignores other company stakeholders such as employees and suppliers. Performance Prism is used for performance design and measurement. Performance measurement in this study is also supported by several methods including weighting with Analytic Hierarchy Process (AHP) to determine the priority value scale of each KPI, Scoring System with Objectives Matrix (OMAX) method, and Traffic Light System to determine the total index value of the company. This research is classified as descriptive research, data collection techniques are carried out by conducting direct interviews with the company and distributing open questionnaires to selected sources, and distributing AHP (Analytic Hierarchy Process) questionnaires. The results of the measurement analysis of PT. Torganda PKS Rantau Kasai has achieved the expected performance with a total index of 7.1307. In this study, there are 3 stakeholders, namely investors (head office) with 10 KPIs, employees with 10 KPIs, and suppliers with 10 KPIs. In total there are 30 KPIs as performance indicators of PT. Torganda PKS Rantau Kasai found 6 KPIs in the green category, 16 KPIs in the yellow category, and 8 KPIs in the red category.